What is the appropriate management of nonfunctioning pancreatic neuroendocrine tumours disclosed on screening in adult patients with multiple endocrine neoplasia type 1?. (1st October 2019) - Challis, Benjamin G.; Casey, Ruth T.; Grossman, Ashley; Newell‐Price, John; Newey, Paul; Thakker, Rajesh V.
Abstract: Multiple endocrine neoplasia type 1 (MEN1) is an inherited tumour syndrome characterised by a predisposition to the development of endocrine tumours of the parathyroid glands, pituitary and pancreas: 30%‐80% of patients with MEN1 develop pancreatic neuroendocrine tumours (pNETs), with metastatic tumours and/or their sequelae contributing to increased morbidity and early mortality. The optimal management of nonfunctioning (NF) pNETs in MEN1 remains controversial. Whilst pancreatic resection is widely recommended for tumours >2 cm, for smaller tumours (≤2 cm) a well‐established consensus guiding the indications for surgical intervention does not exist. Although total pancreatectomy may be curative for some patients, both short‐ and long‐term complications make this an unsatisfactory option for many patients. For small (<2 cm) MEN1 NF‐pNETs, some clinicians advocate surveillance based largely on retrospective data that suggest 50%‐80% of these lesions are stable over time and infrequently exhibit accelerated growth rates. It is increasingly recognised, however, that NF‐pNETs exhibit unpredictable malignant behaviour that is not determined by tumour size alone, thereby prompting other clinicians to advocate surgery for all MEN1 NF‐pNETs, irrespective of size. Such uncertainty poses clinical management challenges with regards to the timing and extent of surgery, which is further hindered by the inability to stratify patients based on predicted tumour behaviour. It is therefore critical that future MEN1 research initiatives include: (a) the discovery of biomarkers that better predict tumour behaviour; (b) the evaluation of medical therapies that may delay, or even prevent, the need for pancreatic surgery; and, ultimately, (c) improvement in the quality of life for individuals with MEN1. Here, based on the published literature, we address the Clinical Question, 'What is the management of NF‐pNETs disclosed on screening in adult patients with MEN1?'.